The Best Practices Of People Development System For Startup Company: Case Study Of Survived Startups in Bandung - Keukeu Gustine, Izky; Pritasari, Adita (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Nowadays many startup companies in Indonesia are growing. The growth and development of startup companies have a positive effect on the country's economic development by creating jobs. Bandung is one of the cities in Indonesia with the many startup growing that are behind the creative industry. Even though many startups can grow up successfully, however,there is also Startup that cannot sustain and must end up with failure. One of the causes of startup failures is the lack of handling of human resources, especially in people development. Whereas people have the main role to develop the company. Moreover, the limited human resources in startup companies make management as if not important. When a startup company cannot develop their people, the company is ready to fail. Responding to the problem, this research was conducted to explore how to develop people at a startup company based on best practices in startup companies located in Bandung city. This study uses qualitative data analysis and semi-structured interviews, exploring how startup companies successfully to developed people used of human resource management concepts and experience from startup company owners. Human Resource Management used consists of four stages to describe the development of the company. The Recruitment and Selection stage explain how the companies look for prospective employees, the criteria needed and their selection. For the Training and Developing Employees stage, described the practices used by startup companies for employees to grow. Then for the Performance Appraisal stage, explained about practices that are suitable to be used to measure performance and action on the performance. Whereas in the Remuneration stage is shown the salary system and facilities provided in startup companies. In addition, there is a description of the experience in the form of tips taken by startup company owners when they fail in running their company. Startup companies in Indonesia can use these people development practices for startup companies to sustain or failure, as these practices have been used by seven startup companies in Bandung with different industry types.Â Keyword: Bandung, HRM, People Development, Startup